Changes in microbiome composition after fecal microbiota transplantation via oral gavage and magnetic navigation technology-assisted proximal colon/cecum enema in antibiotic knock-down rats: a comparative experimental study - Xian-Jie Bai; Yu-Chen Mei; Jia-Tong Zhao; Zhi-Ren Chen; Chen-Xi Yang; Xiao-Juan Dong; Jia-Wei Yu; Lin-Biao Xiang; Er-Zheng Zhou; Yong Chen; Jia-Yi Hao; Zhi-Jie Zhang; et al. (BMC Microbiology)
Abstract Background Fecal microbiota transplantation (FMT) transfers fecal matter from a donor into the gastrointestinal tract of a recipient to induce changes to the gut microbiota for therapeutic benefit; however, differences in the composition of gut microbiota after FMT via different donor material delivery routes are poorly understood. In this study, we first developed a novel technique for FMT, magnetic navigation technology(MAT)-assisted proximal colon enemas, in healthy Sprague–Dawley rats. Besides, the difference in fecal microbiota composition after FMT via oral gavage and proximal colon/cecum enemas was determined in antibiotic knock-down rats, in addition to the impact on intestinal barrier function. Methods A device consisting of an external magnet and a magnet-tipped 6 Fr tube was used in the MAT group (n = 6), and the control group (n = 6) where fecal matter was delivered without magnetic navigation. The feasibility and safety of this method were assessed by angiography and histology. Next, the fecal microbiota of donor rats was transplanted into antibiotic knock-down rats via oral gavage (n = 6) and MAT-assisted proximal colon/cecum enema (n = 6) for a week. Analysis of fecal 16 S rRNA was conducted to determine differences in the composition of gut microbiota between different groups. The rat intestinal barrier integrity were evaulated by H&E and ZO-1/MUC2 immunofluorescence staining. Results The end of the fecal tube could be placed in the cecum or proximal colon of rats in MAT group; however, this was rarely achieved in the control group. No colon perforation or bleeding was detected in either group. After fecal microbiota transplantation, the microbiota α-diversity and β-diversity were comparable among the different delivery routes.At the family level, the relative abundances of Muribaculaceae, Oscillospiraceae, and Erysipelotrichaceae were higher in the gavage treatment group, whereas Lactobacillaceae and Saccharimonadaceae were higher in the enema treatment group (all p < 0.05). FMT by enema was superior to gavage in maintaining the integrity of the rat intestinal barrier, as assessed by an elevation in the density of goblet cells and increased expression of mucin-2. Conclusions Fecal microbiota tube placement using magnetic navigation was safe and feasible in rats.Different delivery route for FMT affects the gut microbiota composition and the integrity of the rat intestinal barrier. Future experimental designs should consider the colonization outcomes of critical microbial taxa to determine the optimal FMT delivery routes in scientific research as well as clinical practise.